2021
DOI: 10.1093/schbul/sbab080
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance Model of Heart Rate Variability and Pulse Wave Velocity in Psychotic and Nonpsychotic Disorders

Abstract: Objectives Patients with psychiatric disorders have an increased risk of cardiovascular pathologies. A bidirectional feedback model between the brain and heart exists widely in both psychotic and nonpsychotic disorders. The aim of this study was to compare heart rate variability (HRV) and pulse wave velocity (PWV) functions between patients with psychotic and nonpsychotic disorders and to investigate whether subgroups defined by HRV and PWV features improve the transdiagnostic psychopathology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…HRV parameters can be used to noninvasively assess the dynamic homeostasis of sympathetic and parasympathetic nerves ( Sgoifo et al, 2015 ). Previous studies of depression have also found that the decrease in HRV was correlated with depression ( Sgoifo et al, 2015 ; Borrione et al, 2018 ; Zhang et al, 2021 ) and suggested that the ANS is 1 of the main neural pathways activated by chronic endogenous and exogenous stress. In conditions associated with chronic stress, such as depression and epilepsy, the sympathetic nervous system can be continuously activated while parasympathetic output is suppressed, and impaired autonomic homeostasis can be reflected by decreased HRV ( Won and Kim, 2016 ).…”
Section: Discussionmentioning
confidence: 83%
“…HRV parameters can be used to noninvasively assess the dynamic homeostasis of sympathetic and parasympathetic nerves ( Sgoifo et al, 2015 ). Previous studies of depression have also found that the decrease in HRV was correlated with depression ( Sgoifo et al, 2015 ; Borrione et al, 2018 ; Zhang et al, 2021 ) and suggested that the ANS is 1 of the main neural pathways activated by chronic endogenous and exogenous stress. In conditions associated with chronic stress, such as depression and epilepsy, the sympathetic nervous system can be continuously activated while parasympathetic output is suppressed, and impaired autonomic homeostasis can be reflected by decreased HRV ( Won and Kim, 2016 ).…”
Section: Discussionmentioning
confidence: 83%
“…TNF-α levels have been reported to be elevated in patients with depression ( 29 31 ), unchanged ( 32 ), and decreased ( 33 ). One possible explanation for this inconsistency is that different TNF-α expression patterns may occur in different clinical subtypes of depressive episodes ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…People with psychotic illness have lower resting state heart rate variability and respiratory sinus arrhythmia compared to controls [139][140][141][142][143] , and individual differences in heart rate variability and/or respiratory sinus arrhythmia have been associated with emotion regulation 144 , psychiatric symptom burden 142 , cognitive performance 143,145,146 , and functioning in this clinical population [142][143][144][145][146] . Notably, these autonomic responses are malleable through biofeedback training [147][148][149][150] , breathing retraining 147,150 , mindfulness practice 151 , and physical exercise 149,152 .…”
Section: [H1] Resilience Factors For Psychosismentioning
confidence: 99%